The Importance of ESP In Learning Basic English For Engineering Students - Setyandari, Ana (Jompa Research and Development, 2022)
This study explores the linguistic demands of engineering students and their specific needs regarding English learning resources in the context of Widya Dharma University's Engineering department. Focusing on students in their third and fifth semesters, the research employs a descriptive qualitative approach to identify gaps in understanding these linguistic needs and the role of English for Specific Purposes (ESP) in enhancing their language skills. Data collection utilizes a questionnaire to gather insights from the student population. The findings underscore the critical role of ESP in bolstering engineering students' language competence, thereby enhancing their prospects in the global job market. This study provides valuable insights into tailoring English language resources to better meet the academic and professional needs of engineering students.